Creation of a Domestic Hybrid Truck with the Maximum Degree of Localization - Sergey N. Poddubko; Alexander V. Belevich; Ivan P. Kravtsov; Mikhail V. Kalinin; Pavel E. Shabanau (Механика машин, механизмов и материалов)
Parallel hybrid power units (HPU) of vehicles are considered, which include an internal combustion engine (ICE), one or more electric motors (EM) that can operate either jointly or separately, a planetary summing mechanism, a bypass battery, and a control system. Various combinations of ICE and EM operation modes are shown, which provide high energy efficiency when driving a car both on highways and in urban conditions. On the basis of the application of this HPU type, the kinematic scheme and layout of the domestic hybrid truck on the chassis of MAZ-5340C5 with a high degree of localization is proposed. The structure of the power unit and the design of the HPU mechatronic module are developed. Different variants of the HPU operating modes are considered.